Teachers’ Perceptions of the Use of Learning Management Systems in Improving Teaching Effectiveness - Koesrini, Juliati; Suhartono, Robertus Heru Setyo; Arafah, Muhammad (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study analyzes teachers’ perceptions of Learning Management System (LMS) use in enhancing teaching effectiveness, focusing on its impact on learning planning, implementation, and evaluation. Using a mixed-methods sequential explanatory design, the research involved a quantitative survey of 150 teachers from Malang, Semarang, and South Sulawesi, followed by in-depth interviews with 15 teachers. Quantitative data were examined using descriptive and comparative analyses, while qualitative data were analyzed thematically. The findings show that most teachers view LMS positively, particularly for material access and student interaction, though challenges remain in digital literacy and infrastructure. Institutional support and training are key to optimizing LMS use. The study concludes that positive teacher perceptions significantly enhance teaching effectiveness, offering theoretical insights into technology adoption in education and practical recommendations for sustainable LMS integration in schools.